2022
DOI: 10.3389/frwa.2021.771764
|View full text |Cite
|
Sign up to set email alerts
|

FluOil: A Novel Tool for Modeling the Transport of Oil-Particle Aggregates in Inland Waterways

Abstract: Spilled oil in inland waterways can aggregate with mineral and organic particles to form oil-particle aggregates (OPAs). OPAs can be transported in suspension or deposited to the bed. Modeling the fate and transport of OPAs can provide useful information for making mitigation decisions. A novel open-source tool, FluOil, is developed to predict where OPAs may deposit and when they arrive in affected river/lake reaches by implementing the random walk particle tracking algorithm to represent the advection, diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The deposition of OPAs on the downstream riverbed varied with the properties of the oil, sand, and natural environment. Interested readers may refer to our previous study for more information on the formation and transport of OPAs (Wang et al, 2020b;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition of OPAs on the downstream riverbed varied with the properties of the oil, sand, and natural environment. Interested readers may refer to our previous study for more information on the formation and transport of OPAs (Wang et al, 2020b;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The spilled oil may transform into a film, droplet, emulsion, aggregate, or other forms within 24 h of the spill (Afenyo et al, 2016;Brussaard et al, 2016), which brings potential challenges to the modeling field. Compared with the development of tools for oil spills in the ocean (Keramea et al, 2021;Zhao et al, 2021), studies on oil transportation in inland waterways are limited (Goeury et al, 2014;Kvočka et al, 2021), and new attempts at model optimization and calibration are still made by researchers around the world (Jiang et al, 2021;Li et al, 2022).…”
mentioning
confidence: 99%
“…This includes particle size distribution which is an important factor for modeling the fate and transport of oil spills, since the particle size distribution can affect the settling velocities and the duration of settling of the OPAs. 53,56 Moreover, an OPA formation model such as A-DROP can be coupled with a hydrodynamic model to investigate the formation and transport of OPAs in rivers and lakes. 57,58…”
Section: Discussionmentioning
confidence: 99%
“…The studies of OPAs can be traced decades ago, where the afterward studies were extended on OPAs in different environments including freshwater systems, , shorelines, , or deeper waters in the oceans. , The modeling of the OPAs was investigated regarding their formation, distribution, settling, and transport. The experimental and modeling results showed that denser OPAs can engulf the spilled oil under water, which is a crucial formation mechanism for submerged oil in marine environments. Consequently, many models studied the existence of OPAs by introducing the concept of oil trapping efficiency (OTE), which denoted the ratio between the content of the oil trapped by OPAs and the content of oil initially existed.…”
Section: Introductionmentioning
confidence: 99%